Pengaruh PENGARUH BERKUMUR REBUSAN DAUN SIRIH HIJAU (PIPER BETLE LINN) TERHADAP pH SALIVA PADA SISWA KELAS III DAN IV DI SEKOLAH DASAR NEGERI JINGAH HABANG ILIR KECAMATAN KARANG INTAN KABUPATEN BANJAR KALIMANTAN SELATAN: - Sahibul Firda; Ida Rahmawati; Isnawati Isnawati; Naning Kisworo Utami (Poltekkes Kemenkes Banjarmasin, 2026)
Betel leaf is a plant that has natural antibacterial properties. Gargling with betel leaf decoction is effective in changing the pH of saliva. This benefit comes from the essential oils in betel leaves, which contain phenolic compounds that are bactericidal and bacteriostatic. These compounds inhibit the growth of oral bacteria such as Streptococcus mutans, thereby preventing acid production by bacteria. This study aims to determine the effect of gargling green betel leaf decoction on salivary pH in class III and IV students at Jingah Habang Hilir State Elementary School. This type of research is a quasi experiment with a one group pretest posttest design. Sampling using Purposive Sampling technique with a total of 30 people. The data analysis test used is Paired Sample T-test. The results showed that the average pH of saliva before gargling green betel leaf decoction was 6.28 and after gargling green betel leaf decoction was 7.08. The results of the Paired Sample T-test showed ρ=0.000 <α=0.05 which means there is an effect of gargling green betel leaf decoction on salivary pH. In this study, it can be concluded that there is an effect of gargling green betel leaf decoction on salivary pH in class III and IV students at Jingah Habang Hilir State Elementary School. It is recommended to utilize green betel as a herbal mouthwash that has minimal side effects and is effective in helping to neutralize salivary pH thanks to its essential oil content.